Islamic Family Education in the Digital Era: An Integrative Framework of Tawḥīd-Based Character Formation - Wisnu Wardana; Imam Mudhofir; Muhammad Hilmi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the foundations, objectives, principles, and parental roles in Islamic family education and to formulate an integrative conceptual framework for strengthening tawḥīd-based character formation in the digital era. Methodology: This study employed a qualitative library research design. Data were collected through systematic literature review of classical and contemporary Islamic education sources, academic journal articles, and scholarly books. Data analysis used descriptive-analytical and interpretative methods with thematic categorization. Microsoft Word was used for data organization and documentation Main Findings: The study reveals that Islamic family education is fundamentally grounded in tawḥīd as the central value system shaping children’s moral and spiritual development. Five core principles were identified: tawḥīd orientation, parental role modeling, consistency, affection-based communication, and structured habituation with supervision. Contemporary challenges require adaptive yet principled implementation strategies within Muslim families. Novelty/Originality of this study: This study proposes an integrative conceptual framework that systematically connects theological foundations, educational principles, parental roles, and digital-era challenges. It advances existing knowledge by synthesizing fragmented discussions into a coherent model that bridges classical Islamic pedagogy with contemporary social realities.